Intellectual Capital in The Business Model of An Economic Unit And Its Competitiveness at The Time Of COVID-19 - Katarzyna CHŁAPEK; Sylwia KRAJEWSKA (Communications of International Proceedings, 2020)
Effective and informed business models are a challenge especially in terms of their impact on competitiveness of units. In the reality of the COVID-19 pandemic, intellectual capital has a special place in a business model. The aim of this article is to draw attention to the impact of intellectual capital, revealed in a business model, on the competitiveness of a unit and its particular importance in the current conditions of economic life. The article uses official financial and non-financial data of KGHM and results of the most popular business rankings. The research shows that there is a link between competitiveness of a unit and its intellectual capital activities in the business model. In the context of the threat to continuation of activities of many units, the article reveals the need for further research in the area of adjusting the business model to specific operating conditions, taking into account the role of intellectual capital.  Only a re-examination and a substantial modification of the business model, based on intellectual capital, may enable survival in a crisis situation. Research of the study and formulated conclusions can be useful to both scientists and practitioners interested in opportunities to support units in tackling the challenges posed by COVID-19.
Keywords: Intellectual Capital; Business Model; COVID-19; Non-Financial Data.